(untitled) (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
The illicit trafficking and abuse of narcotics in Indonesia have reached alarming levels, with the number of users reaching 5.9 million people. This situation has placed Indonesia in a state of narcotics emergency. Factors such as the vast geographical area and large population have made the country a strategic market for drug trafficking in Southeast Asia. If not addressed immediately, this will pose a serious threat to the future of Indonesia’s younger generation. Therefore, a solutive approach is needed by actualizing the values of Pancasila in community life. This study aims to analyze how the actualization of Pancasila values can serve as a solution to combat drug abuse, particularly in the Pupuan Bengkulu region. Through an applicative approach to the five principles of Pancasila, it is hoped that effective strategies can be created to tackle drug trafficking and abuse while strengthening national identity based on Pancasila.